Vibration‐Induced Emission: Tunable Photoluminescence Including White‐Light Emission Based on Noncovalent Interaction‐Locked N, N′‐Disubstituted Dihydrodibenzo[a, c]phenazines (Advanced Optical Materials 12/2018). Issue 12 (19th June 2018) - Wang, Jie; Yao, Xuyang; Liu, Yang; Zhou, Haitao; Chen, Wei; Sun, Guangchen; Su, Jianhua; Ma, Xiang; Tian, He
Abstract : Typical vibration‐induced emission (VIE) molecules, as studied by Xiang Ma and co‐workers in article number1800074, are graphically simplified as two butterflies with different excitation conformations: as the stretched state with red photoluminescence emission and the folded state with blue photoluminescence emission. The utilized supramolecular assembling strategy influences the specific positions of VIE molecules and works like Tai Chi to fuse the two states of VIE molecules, thus achieving a reversible photoluminescent control from red to blue.